Gradual mechanical deformation discernible devices based on flexible self-powered Ⅲ-nitride pin photoelectrochemical piezo-phototronics - Junjun Xue; Xinya Tao; Xu Wang; Tongdao Pan; Zhouyu Chen; Guanyu Xu; Qing Cai; Pengfei Shao; Yushen Liu; Zengli Huang; Ting Zhi; Bin Liu; et al. (Materials Today Advances)
The piezoelectricity of Ⅲ-nitrides distinguishes themselves from traditional semiconductors and evoke two novel effects: the piezotronic and piezo-phototronic effect. As a typical representative in piezotronics, due to the re-distribution of piezoelectric charges, the piezoelectric nanogenerator can directly make impulse-type electric response on dynamic strain. This determines the piezoelectric nanogenerator to be more sensitive to rapid motion and unable to make effective response on the slow deformation. Here we have proposed a configuration of solid-state electrolyte flexible piezo-phototronics based photoelectrochemical photodectors (PEC PD) constructed by exfoliated Ⅲ-nitride pin membrane. By inserting InGaN single quantum well into GaN pn-junction, the carrier screening is diminished by enlarged depletion region of pin junction, which enhances the ability of piezo-polarization charge on modifying the energy band at interface; moreover, the carrier transport within pin junction can be influenced by adjusting the quantum-confined-Stark effect. Thereout, compared to pin-PEC PD without deformation, when the pin-PEC PD are under the convex/concave bending, the photocurrent of the PD shows increase/decrease, respectively, which can achieve the function of slow deformation recognition. The miniaturized flexible PEC cell equipped with the bluetooth-linked portable electrochemical workstation shows tremendous potential in the field of application of strain gauges with complex operation.